2021
DOI: 10.25092/baunfbed.829863
|View full text |Cite
|
Sign up to set email alerts
|

Bazı nar ürünlerinin antioksidan özellikler ve in-vitro biyoerişilebilirlik açısından değerlendirilmesi

Abstract: In this research, pomegranate molasses, pomegranate sour sauces and pomegranate jams were evaluated in terms of some physicochemical properties including hydroxymethylfurfural, total phenolic content, antioxidant capacity and bioaccessibility. While ascorbic acid of these products ranged between 0.89-19.78 mg 100g-1 , total phenolic contents changed between 31.40-2061.10 mg gallic acid equivalent 100g-1. Antioxidant capacities of the products were determined as 34.01-2377.52 mg trolox equivalent 100g-1 with DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…The hydrolysis of the glycosidic monomers and the phenolic oligomers found in the PJC releases the different phenolic aglycons and exposes more hydroxyl groups, which react with the total phenolics assay reagent (Folin–Ciocalteu). Our conclusions were consistent with the conclusions of other researchers [ 1 , 3 , 6 ], while the results previously reported [ 11 ] had higher values than our findings. The differences in total phenolic content of PJC between these studies are anticipated to be due to influences such as the types of grenades, climate, cultivars, production, extraction, evaporation, heat performances, and soil [ 3 ].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The hydrolysis of the glycosidic monomers and the phenolic oligomers found in the PJC releases the different phenolic aglycons and exposes more hydroxyl groups, which react with the total phenolics assay reagent (Folin–Ciocalteu). Our conclusions were consistent with the conclusions of other researchers [ 1 , 3 , 6 ], while the results previously reported [ 11 ] had higher values than our findings. The differences in total phenolic content of PJC between these studies are anticipated to be due to influences such as the types of grenades, climate, cultivars, production, extraction, evaporation, heat performances, and soil [ 3 ].…”
Section: Resultssupporting
confidence: 94%
“…Flavonoids are a subclass of phytochemicals with strong bioactive potential and free radical scavenging capacities, and they positively affect human health [ 3 ]. As illustrated in Table 1 , the total flavonoid content of the PFC was 82.58 ± 0.75 mg/100 g. These data agree with those of previously published studies [ 1 , 3 , 6 ], while other results previously reported [ 11 ] showed a higher value than our findings. The reasons for the differences in the total flavonoid content of the PJC between these investigations are similar to the reasons for the differences in the total phenolic content.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The Hunter L*, a* and b* values of the samples were given in Table 3. Concentration was caused to the darkening of the samples with non-enzymatic browning reactions (35). For this reason; while the L* and b* decreased, a* increased of the bitter orange sour and bitter orange sauce supplemented with CMP.…”
Section: Color Measurementmentioning
confidence: 99%